2019
DOI: 10.1177/0011128719839376
|View full text |Cite
|
Sign up to set email alerts
|

The Strain From Procedural Injustice on Parolees: Bridging Procedural Justice Theory and General Strain Theory

Abstract: The procedural justice literature explains why people obey the law. However, prior research has largely neglected the implication of procedural justice in the correctional context in general and in parole efficacy in particular. In an attempt to bridge the propositions of procedural justice and general strain theory, this study assesses the effect of parolees’ perceived procedural injustice on their success in reentry. Using data from a longitudinal study of prisoner reentry, we investigate the nexus of proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…As this relates to GST, when the interaction is perceived as procedurally just, then it will likely not be conceived as a strain. Agnew noted, however, that when relevant justice rules are violated—in this case, when individuals perceive that they were unfairly treated by police—then the event may represent an unjust strain (see also Liu et al., 2020). Among other conditions, Agnew (2001, p. 331) suggested that procedural injustice is likely present when individuals have no voice during the infliction of strain, question the legitimacy of those inflicting said strain, do not trust those inflicting strain, and believe that the decision‐making process conflicts with moral values.…”
Section: Consequences Of Unfair Treatment By Policementioning
confidence: 99%
“…As this relates to GST, when the interaction is perceived as procedurally just, then it will likely not be conceived as a strain. Agnew noted, however, that when relevant justice rules are violated—in this case, when individuals perceive that they were unfairly treated by police—then the event may represent an unjust strain (see also Liu et al., 2020). Among other conditions, Agnew (2001, p. 331) suggested that procedural injustice is likely present when individuals have no voice during the infliction of strain, question the legitimacy of those inflicting said strain, do not trust those inflicting strain, and believe that the decision‐making process conflicts with moral values.…”
Section: Consequences Of Unfair Treatment By Policementioning
confidence: 99%
“…It can be caused by emotional disturbance—as observed in expressive crimes such as assaulting and battering (Cohn & Rotton, 2003; Miethe & Drass, 1999). However, more often reoffending results from deviant peer association (Boman & Mowen, 2017; Mowen & Boman, 2018), anti-social culture (Skilling & Sorge, 2014; Smith et al, 2012; Walters & Lowenkamp, 2016), and financial difficulty (Bushway, 2004; Garcia-Hallett, 2019; Liu et al, 2020c; Travis, 2002). Family support is found to neutralize reentry challenges such as financial difficulty, social rejection and isolation (Duwe & Clark, 2013; Liu & Visher, 2019; Mowen & Visher, 2016; Visher & Courtney, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Public control can be various services formally institutionalized and provided by governmental agencies such as programs operated by criminal justice and social service agencies (Bursik, 1988; Kornhauser, 1978). Given that addiction and mental health challenges are primary predictors of drug use (Bowles et al, 2012; Liu et al, 2020a), reentry programs such as counseling and drug treatment programs should be conceptualized as proxies of public social control on former prisoners. Reentry services that provide mental health counseling and drug treatment are expected to inhibit drug use for this social group.…”
Section: Prior Studies On Social Control and Illicit Drug Usementioning
confidence: 99%